المعايير النصية لدى روبرت دي بوجراند في ديوان "همسات الصبا" للشاعر الليبي رجب الماجري: دراسة نقدية تحليلية - Milood Mustafa Ashur
Libyan poetry has interacted with time and space, thereby expressing the Libyan people’s hopes as well as pains. It has also chronicled the battles of Jihad againstinvaders, and fostered the idea of belonging among the people of the Islamic nation.However, Libyan poetry has not been subjected to systematic criticism according toscientific principles and rules. Since the critical works in Libya still lack in depth andopenness, and dominate the critic’s mood rather than a scientific approach, Libyan literature has not gained any fame within the Arab region and internationally. The research problem was that Al-Majiri’s poetry is considered as a vivid example of the crisis experienced by that poetic output, as well as its lack of criticism and systematic analysis. Therefore, the research aims to provide a critical study of Al-Majiri’s Anthology that discusses the artistic characteristics of his poems from the perspective of modern text linguistics. Specifically, the study focuses on the extent to which these poems achieved the seven standards of the Text Grammar Theory developed by De Bojerand and Dressler (1981) that is considered the latest criticism theory. Several approaches were utilized: descriptive, analytical and inductive. The findings revealed that Al-Majiri created wonderful literary texts in terms of coherence and cohesion. His poems portrayed the will of the Libyans to hold their principles, and carried noble humanitarian purposes with an Islamic character. The poems were integrated with the poet’s ideas and thoughts internally and externally as well as with other texts through which he expressed his doctrine in the production of poetic creativity with reference to the Islamic religion, hence, serving the homeland and the citizen. The study emphasized the importance of the Text Grammar Theory as a critical approach that describes the poetic text and reveals its literary value by discussing it in the context of communication and social and psychological factors affecting its acceptance. The researchers recommended that further critical studies should be carried out to reveal the attractive aspects of the Libyan literature so that it can assume high prestige at the Arabic and global levels. It was also recommended that future researchers should pay attention to the seven scientific standards and should study the internal intertextuality because it reveals the relation between the text and the poet, and unravels the cover on the important aspects of the poet’s character. Finally, the researcher suggested that terminologies or terms in text science should be unified.